Molecular Characterisation of Vibrio Vulnificus Isolated from Cockles (Anadara Granos A) and Shrimps (Panaeus Indicus) in Malaysia - Tengku Ahmad, Tengku Ahbrizal Farizal (2001)
A prevalence study was conducted to determine the presence of Vibrio vulnificus in cockles (Anadara granosa) and shrimps (Panaeus indicus) in Malaysia. Out of 19 samples examined from cockles and 42 samples from shrimps, 10 and 12 samples were positive for V. vulnificus respectively. Twenty-nine strains from cockles and 21 strains from shrimps were selected for further studies. The strains isolated from cockles and shrimps comprised both biotype 1 (17 of 29) and biotype 2 (15 of 21). All strains were tested for their susceptibility to selected antimicrobial agents and were examined for the presence of plasmid DNA. The antimicrobial susceptibility patterns indicated that most of the strains from cockles were resistant to kanamycin (96.55%), carbenicillin (86.21%) and bacitracin (82.76%). An strains from shrimps were resistant to penicillin (100%),gentamicin. Twenty-six and 18 antibiotic resistance patterns were observed from cockles and shrimps, respectively. The MAR index for cockle strains was between 0.13 and 0.8, whereas, for shrimp strains, the MAR index was between 0.067 to 0.73. Thirty strains were found to contain plasmid DNA, ranging in sizes from 1.5 to 35.8 megadalton. Only five strains (strain VC9, YC26, YS6, VSl8 and YSI9) of V. vulnificus in this study harboured a large plasmid of 35.8 MDa. The conjugation study was done to investigate the transferability of the R plasmids among V. vulnificus strains to recipient E. coli K12 strain. However, no R plasmid transfer was observed. RAPD-PCR fingerprinting was used to differentiate V. vulnificus strains. Primers GEN 1-50-01 (5'-GTGCAATGAC3-') and GEN 1-50-08 (5'-GGAAGACAAC3-') illustrated polymorphism in most strains tested, with the DNA band sizes ranging from 0.25 to 10.0 kilobase pair. Dendrograms generated showed that primer GEN 1-50-01 illustrated 46 RAPD patterns. All strains were well separated at 100% similarity level, except strain VC16, VC23 and VS17, which were found to be clustered together. Primer GEN 1-50-08 illustrated 47 RAPD patterns and all strains were well separated into single strains at 85% similarity level. V. vulnificus strains from both sources were also analysed by SDS-PAGE fingerprinting to observe the protein profiles. Dendrogram generated showed that V. vulnificus strains illustrated 50 protein profiles, with sizes ranging between 3.4 to 212 kilodalton. The cluster analysis from both RAPD profiles and protein profiles indicates that there is a high degree of genetic diversity within V. vulnificus strains examined.